Risks for Adverse Events by Sex and Age After Prescription Opioid Dose Reduction - Metz, Verena E.; Palzes, Vanessa A.; Binswanger, Ingrid A.; Altschuler, Andrea; Poulsen, Melissa N.; Ahmedani, Brian K.; Andrade, Susan E.; Clark, Robin E.; Hechter, Rulin C.; Horberg, Michael A.; Sanchez, Katherine; Bailey, Steffani R.; et al. (American journal of preventive medicine, 2025)
Prescription opioid dose reductions can raise the risk of adverse events for patients on long-term opioid therapy for noncancer pain. Evidence on whether risks differ by age or sex is needed to support tailored clinical decision-making. In 2024, a secondary analysis of an observational cohort study was conducted across 8 U.S. healthcare systems analyzing electronic health records and claims data from a prescription opioid registry (excluding buprenorphine prescriptions) between January 1, 2012, and December 31, 2018, including adults with stable prescription opioid use and a subsequent ≥2-month dose reduction period (n=60,040), yielding 600,234 dose reduction periods as the analytic sample. Differences in the association between dose reduction level (1% to <15%, 15% to <30%, 30% to <100%, and 100% from baseline) and potential adverse events (emergency department visits, opioid overdose, all-cause mortality, and benzodiazepine prescription fills) in the month after dose reduction by sex and age group were examined by including interaction terms in logistic regression models. Of the 600,234 dose reduction periods, 346,733 were among women, with a mean age of 57.5 (SD=13.2) years for women and 56.7 (SD=12.1) years for men. Associations between dose reduction levels and potential adverse events did not differ significantly by sex, but differed by age for emergency department visits: patients aged 40–64 and ≥65 years with dose reductions of 30% to <100% had lower odds than those aged 19–39 years (adjusted ratio of OR=0.87, CI=0.80, 0.96; adjusted ratio of OR=0.82, CI=0.74, 0.91, respectively). Patients aged <40 years may benefit from closer monitoring in the month after dose reduction, given their higher odds of an emergency department visit.